Life Cycle Assessment of the Solok Rice Production System in the Gunung Talang District, Solok Regency, West Sumatra - Aswin, Shabrina Nashya; Asben, Alfi; Nazir, Novizar (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
Solok rice is an important agricultural commodity that contributes significantly to the economic prosperity of the West Sumatra region. As indigenous knowledge from West Sumatra, the development and preservation of Solok rice can stimulate a nationwide increase in rice production. The cumulative effects of the entire sequence of activities comprising Solok rice production will impact environmental quality due to increased output. Therefore, a Life Cycle Assessment (LCA)-based environmental impact assessment of Solok rice production is necessary. The analysis results indicate that the total greenhouse gas emissions from Solok rice production equal 1.94 kg CO2eq per kilogram of rice. The subsequent potential effects include acidification at a rate of 0.06 kilograms of SO2-equivalent per kilogram of rice and eutrophication at a rate of kilograms of PO43-equivalent per kilogram of rice. The calculation of net energy yielded a Net Energy Value (NEV) of 18.36 GJ and a Net Energy Ratio (NER) greater than 1. To mitigate emission values in the land and environment, the current system improvement emphasizes fertilizer consumption, increasing the use of organic materials, and instituting production waste recycling.